Floods and weather in 1342 and 1343 in the Carpathian basin - Kiss, Andrea (Journal of Environmental Geography, 2009)
Concerning weather, weather-related extremes and catastrophic consequences, 1342 was an extraordinary year in most parts of Central Europe, even in such an extraordinary decade as the 1340s. Accounting with the seven flood events (including one Danube flood) mainly of great magnitude, at present 1342 is the most important known flood year of medieval Hungary. Moreover, in this year extraordinary weather conditions, such as a mid-autumn snowcover were also reported. However, in the eastern parts of the Carpathian basin not only 1342 but also 1343 was a significant flood year with six reports on flood events occurred in the upper and upper middle sections of the Tisza catchment. In the present study, an overview of these events is provided, based on the information preserved in the most typical contemporary, well-dated source type of medieval Hungary, namely charters. The aim of the study is, on the one hand, to draw attention to the flood and weatherrelated evidence found in charters, and to provide a methodological background for further evaluation and utilisation of this source type in historical weather and flood research, through the very typical example of the years of 1342 and 1343. On the other hand, another aim is to discuss and analyse the unique nature of these two years in medieval Hungary, and (beyond the well-known year of 1342) to draw attention to the, up to now somewhat neglected, year of 1343.